Policy-oriented environmental research: What is it worth?. Issue 86 (August 2018) - Pannell, David J.; Alston, Julian M.; Jeffrey, Scott; Buckley, Yvonne M.; Vesk, Peter; Rhodes, Jonathan R.; McDonald-Madden, Eve; Nally, Simon; Goucher, Garry; Thamo, Tas
Highlights: Evidence about the benefits to society from research is increasingly demanded. Economic models to evaluate the benefits of research exist but have not been applied to environmental research. We outline a framework for estimating the benefits of policy-oriented environmental research. Key elements include defining the counterfactual, time lags and valuing the benefits. Applications to environmental research are especially challenging when the research users are policymakers. Abstract: Environmental and conservation scientists are increasingly being asked to justify their work in terms of benefits to society. This article describes economic theory for conceptualizing the benefits from environmental research, and provides a framework for estimating those benefits. In particular we discuss the evaluation of environmental science that is intended to benefit society through informing policy decisions. The chain between environmental research and its benefits through policy change includes at least four links: the research itself, policy change, behavior change and environmental change. Each of these four stages presents challenges and entails time lags. If any link fails, the chain breaks. The standard economic model of supply and demand, which is used to quantify benefits from research into market goods, can be adapted for application to environmental goods. Improved conceptualization and measurement of benefits from environmental research would assist environmental scientists to: (1) select research topics that are likely to deliver large environmental benefits; (2) design their research in a way that will increase its relevance, usefulness and potential impact on policy and, ultimately, the environment; and (3) make the case for funding particular research proposals. It could assist research agencies or research funders to: prioritize proposed research; make a case for increased funding for environmental research; and identify obstacles to the translation of research into environmental impacts, allowing attention to be focused on addressing these bottlenecks.